2017
DOI: 10.1038/s41598-017-10068-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-based expression profiling of benign prostatic hyperplasia and prostate cancer delineates an immunophilin molecule associated with cancer progression

Abstract: Aberrant restoration of AR activity is linked with prostate tumor growth, therapeutic failures and development of castrate-resistant prostate cancer. Understanding the processes leading to AR-reactivation should provide the foundation for novel avenues of drug discovery. A differential gene expression study was conducted using biopsies from CaP and BPH patients to identify the components putatively responsible for reinstating AR activity in CaP. From the set of genes upregulated in CaP, FKBP52, an AR co-chaper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…FKBP4 was found to be associated with major depressive disorder (Binder et al, 2004;Tatro et al, 2009a,b) and might be critical to early steps in neuronal differentiation (Quintá and Galigniana, 2012), chemotropic guidance of neuronal growth cones (Shim et al, 2009), and regulating neuroprotective activities with calcium channels (Ruan et al, 2008). It was also reported in malignancies like prostate cancer (Bhowal et al, 2017;Joshi et al, 2017) and breast cancer (Ostrow et al, 2009). CCNY knockout can inhibit glioma cell proliferation (Xu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…FKBP4 was found to be associated with major depressive disorder (Binder et al, 2004;Tatro et al, 2009a,b) and might be critical to early steps in neuronal differentiation (Quintá and Galigniana, 2012), chemotropic guidance of neuronal growth cones (Shim et al, 2009), and regulating neuroprotective activities with calcium channels (Ruan et al, 2008). It was also reported in malignancies like prostate cancer (Bhowal et al, 2017;Joshi et al, 2017) and breast cancer (Ostrow et al, 2009). CCNY knockout can inhibit glioma cell proliferation (Xu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The scatterplot shown in Figure 1C depicts genes upregulated in specimens representing poor (relapsed) vs favorable (disease-free) outcomes. Among genes upregulated in patients with poor prognosis (genes depicted in the right upper area in Figure 1C ) were those related to cell proliferation, including MYC and its targets: FKBP4 , 26 SRM , 27 and PAICS . 28 All 4 of these genes were expressed at high levels in DLBCL cell lines relative to normal LN samples (supplemental Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of studies observed that FKBP4 expression was also upregulated in different types of cancers, e.g., head and neck cancer, prostate cancer, glioblastoma, ovarian cancer, colon cancer and so forth [3,6,[18][19][20][21][22]. Particularly, data from Yang's study showed that FKBP4 was significantly upregulated in majority of BC cell lines [5], but its expression status and prognostic merit in LABC still remains unclear.…”
Section: Discussionmentioning
confidence: 99%